Questi tempi: analisi, riflessioni, proposte - Bortolon, Paola (Chimica nella Scuola, 2025)
The article proposes a reflection on some aspects of today’s society’s cognitive and social dimensions. These aspects can affect teaching-learning and limit young people’s volition, autonomy, and determination. With some references to the past situation, simple examples and suggestions are provided to dispel misconceptions and misunderstandings, increase motivation, self-esteem, and self-determination, and make fragility and mistakes perceived as opportunities for growth and resilience.